Efektivitas Proses Produksi Melalui Pengendalian Kualitas pada Part End Plate dengan Metode Lean Six Sigma di PT. GCE - Nur Sahroni; Darajatun, Rizki Achmad (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Competition in the business world is getting tougher, encouraging companies to improve and develop the quality of their production, the quality of the goods or services produced will affect the competition of a company. Making the production process more effective is something that companies must do to increase production results and can affect company costs. PT.GCE is a manufacturing company operating in the Sheet Metal sector and the production process takes place on a job order basis. In the production process, various deviations and obstacles often occur which result in products experiencing non-conformities, both in product form and processing time. The Six Sigma method is a business strategy that is considered capable of improving and maintaining a company's operational excellence. The results of calculations carried out using the DMAIC method in the Part End Plate production process obtained data on 0.048 defects in the non-conforming product category and 0.084 defects in untidy products, so it can be concluded that defects in Part End Plate products are below 3.4 defects out of a million opportunities. From the calculation results, it was found that the factors causing defects in the Part End Plate production process could be caused by several factors experienced, including machine and labor factors. It is necessary to propose improvements that can be made in an effort to reduce the level of product defects in Part End Plate products so that defects no longer occur in the product. Keywords: DMAIC, Manufacture, Quality Control, Six Sigma.